Targeting experimental orthotopic glioblastoma with chitosan-based superparamagnetic iron oxide nanoparticles (CS-DX-SPIONs) - Shevtsov, Maxim (Int J Nanomedicine, 2018)
BACKGROUND: Glioblastoma is the most devastating primary brain tumor of the central nervous system in adults. Magnetic nanocarriers may help not only for a targeted delivery of chemotherapeutic agents into the tumor site but also provide contrast enhancing properties for diagnostics using magnetic resonance imaging (MRI). METHODS: Synthesized hybrid chitosan-dextran superparamagnetic nanoparticles (CS-DX-SPIONs) were characterized using transmission electron microscopy (TEM) and relaxometry studies. Nonlinear magnetic response measurements were employed for confirming the superparamagnetic state of particles. Following in vitro analysis of nanoparticles cellular uptake tumor targeting was assessed in the model of the orthotopic glioma in rodents. RESULTS: CS-DX-SPIONs nanoparticles showed a uniform diameter of 55 nm under TEM and superparamagentic characteristics as determined by T(1) (spin-lattice relaxation time) and T(2) (spin-spin relaxation time) proton relaxation times. Application of the chitosan increased the charge from +8.9 to +19.3 mV of the dextran-based SPIONs. The nonlinear magnetic response at second harmonic of CS-DX-SPIONs following the slow change of stationary magnetic fields with very low hysteresis evidenced superparamagnetic state of particles at ambient temperatures. Confocal microscopy and flow cytometry studies showed an enhanced internalization of the chitosan-based nanoparticles in U87, C6 glioma and HeLa cells as compared to dextran-coated particles. Cytotoxicity assay demonstrated acceptable toxicity profile of the synthesized nanoparticles up to a concentration of 10 μg/ml. Intravenously administered CS-DX-SPIONs in orthotopic C6 gliomas in rats accumulated in the tumor site as shown by high-resolution MRI (11.0 T). Retention of nanoparticles resulted in a significant contrast enhancement of the tumor image that was accompanied with a dramatic drop in T(2) values (P<0.001). Subsequent histological studies proved the accumulation of the nanoparticles inside glioblastoma cells. CONCLUSION: Hybrid chitosan-dextran magnetic particles demonstrated high MR contrast enhancing properties for the delineation of the brain tumor. Due to a significant retention of the particles in the tumor an application of the CS-DX-SPIONs could not only improve the tumor imaging but also could allow a targeted delivery of chemotherapeutic agents.